2015
DOI: 10.3389/fmars.2015.00028
|View full text |Cite
|
Sign up to set email alerts
|

Coupled nitrate N and O stable isotope fractionation by a natural marine plankton consortium

Abstract: The stable nitrogen (N) and oxygen (O) nitrification. Differences in irradiance in the fall incubations resulted in slightly reduced nitrate consumption at low light but had no distinguishable impact on the N isotope effect ( 15 ε) associated with NO − assimilation, which ranged between 5 and 8‰. The 3 late-summer community incubations, in contrast, showed significantly reduced growth rates at low light and more elevated 15 ε of 11.9 ± 0.4‰, compared to 8.4 ± 0.3‰ at high-light conditions. The seasonal diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…This was because the irradiance of LL treatment was already saturated for phytoplankton growth. The saturating light threshold of 140–150 μmol photons m −2 s −1 was generally applied previously for both the laboratory monocultures (Granger et al, ; Needoba & Harrison, ) and the natural marine plankton consortium (Rohde et al, ). Thus, the HL and LL treatments are considered as duplicate samples hereafter.…”
Section: Resultsmentioning
confidence: 99%
“…This was because the irradiance of LL treatment was already saturated for phytoplankton growth. The saturating light threshold of 140–150 μmol photons m −2 s −1 was generally applied previously for both the laboratory monocultures (Granger et al, ; Needoba & Harrison, ) and the natural marine plankton consortium (Rohde et al, ). Thus, the HL and LL treatments are considered as duplicate samples hereafter.…”
Section: Resultsmentioning
confidence: 99%
“…Potentially overlapping N cycle processes, such as NO3 uptake and nitrification, can be tracked via natural variations in the N and oxygen (O) isotopes of NO3. During NO3 uptake, the N and O isotopes are closely coupled, with phytoplankton preferentially consuming 14 N‐ and 16 O‐bearing NO3 such that the ambient NO3 pool becomes enriched in 15 N and 18 O as consumption proceeds (Granger et al ; Rohde et al ). In the upper water column, NO3 uptake by phytoplankton manifests as an equal rise in the δ 15 N and δ 18 O of NO3 (Trull et al ; DiFiore et al ; Rafter and Sigman ), concurrent with a decline in its concentration (δ 15 N, in ‰ vs. N 2 in air, = {[( 15 N/ 14 N) sample /( 15 N/ 14 N) air ] – 1} × 1000; δ 18 O, in ‰ vs. Vienna Standard Mean Ocean Water (VSMOW), = {[( 18 O/ 16 O) sample /( 18 O/ 16 O) VSMOW ] – 1} × 1000).…”
mentioning
confidence: 99%
“…The region is characterized by some of the largest phytoplankton blooms on Earth, which begin in the spring as the mixed layer shoals and light levels rise. Rapidly growing diatoms typically dominate the spring bloom phytoplankton community, driving high rates of NO -3 uptake and export production (Rynearson et al 2013;Alkire et al 2014;Cetinić et al 2015). As silicate concentrations become limiting, diatom growth slows and smaller phytoplankton such as dinoflagellates and coccolithophores become dominant under the nutrient-deplete conditions characteristic of the late summer (Tarran et al 2001;Dandonneau et al 2004; Barton et al 2013).…”
mentioning
confidence: 99%
“…where 1518 ε NAR (assigned as 15‰, Granger et al, 2008; Table S1) is the N and O isotopic fractionation factor of NAR (i.e., 15 ε NAR = 18 ε NAR , Sigman et al, 2005;Granger et al, 2008;Granger et al, 2010;Rohde et al, 2015;Osaka et al, 2018) and 15 ε DENNIR (assigned as 5‰, Granger and Wankel, 2016;Table S1) is the 15 N fractionation factor of DENNIR.…”
Section: Simulation Exercise For Denitrification and Anammox (The Anamentioning
confidence: 99%
“…Studies on 15 N and 18 O fractionation factors revealed that -NO 3 consumption (the assimilatory and dissimilatory reduction of NO 3 -) generally induced a 1:1 increase in the δ 18 O and δ 15 N of NO 3 - (Granger et al, 2008;Granger et al, 2010;Karsh et al, 2012;Rohde et al, 2015;Osaka et al, 2018). This finding prompted the use of the δ 18 O and δ 15 N of NO 3 -to detect NO 3 -consumption in the actual ecosystem as well as investigations on NO 3 isotope anomalies, specifically isotopic deviations from a slope of 1 in the δ 18 O vs δ 15 N of NO 3 (Δ[15, 18]; Sigman et al, 2005), in order to deepen insights into NO 3 -dynamics (Casciotti et al, 2008;Casciotti and Buchwald, 2012;Bourbonnais et al, 2013;Peters et al, 2018;White et al, 2019).…”
mentioning
confidence: 99%